2014
DOI: 10.1128/aem.01849-14
|View full text |Cite
|
Sign up to set email alerts
|

WblAch, a Pivotal Activator of Natamycin Biosynthesis and Morphological Differentiation in Streptomyces chattanoogensis L10, Is Positively Regulated by AdpAch

Abstract: bDetailed mechanisms of WhiB-like (Wbl) proteins involved in antibiotic biosynthesis and morphological differentiation are poorly understood. Here, we characterize the role of WblA ch , a Streptomyces chattanoogensis L10 protein belonging to this superfamily. Based on DNA microarray data and verified by real-time quantitative PCR (qRT-PCR), the expression of wblA ch was shown to be positively regulated by AdpA ch . Gel retardation assays and DNase I footprinting experiments showed that AdpA ch has specific DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Similar results were observed in other groups who investigate the mechanisms underlying wblA regulating antibiotic production in streptomyces (Geiman et al 2006;Lee et al 2010;Yu et al 2014). It was shown that Wbl proteins may change their regulatory function in response to dormancy signals, including O 2 and nitric oxide (NO), via their iron-sulphur cluster (Nguyen et al 2006).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results were observed in other groups who investigate the mechanisms underlying wblA regulating antibiotic production in streptomyces (Geiman et al 2006;Lee et al 2010;Yu et al 2014). It was shown that Wbl proteins may change their regulatory function in response to dormancy signals, including O 2 and nitric oxide (NO), via their iron-sulphur cluster (Nguyen et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…; Yu et al . ). It was shown that Wbl proteins may change their regulatory function in response to dormancy signals, including O 2 and nitric oxide (NO), via their iron‐sulphur cluster (Nguyen et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a global repressor, WblA affects doxorubicin (DXR), tautomycetin, and daptomycin biosynthesis in their natural host strains Nah et al, 2012;Kim et al, 2014). However, WblA activates natamycin biosynthesis in Streptomyces chattanoogensis (Yu et al, 2014).…”
Section: The Regulatory Cascades Of Antibiotic Production In Streptommentioning
confidence: 99%